2006
DOI: 10.1038/sj.bjp.0706827
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of selective 5‐HT6 receptor ligands determined by monitoring 5‐HT6 receptor‐mediated cAMP signaling pathways

Abstract: 1 Two novel selective 5-HT6 receptor ligands E-6801 (6-chloro-N-(3-(2-(dimethylamino)ethyl)-1H-indol-5-yl)imidazo[2,1-b]thiazole-5-sulfonamide) and E-6837 (5-chloro-N-(3-(2-(dimethylamino)ethyl)-1H-indol-5-yl)naphthalene-2-sulfonamide) were investigated and compared to the putative 5-HT6 receptor antagonists SB-271046 (5-chloro-N-(4-methoxy-3-(piperazin-1-yl)phenyl)-3-methylbenzo [b] thiophene-2-sulfonamide) and Ro 04-06790 (N-(2,6-bis(methylamino)pyrimidin-4-yl)-4-aminobenzenesulfonamide) using a cAMP-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…It is therefore an apparent paradox that E-6801, a full 5-HT 6 receptor agonist in in vitro studies (Holenz et al 2005;Romero et al 2006Romero et al , 2007, caused a dose-related restoration of natural forget- Fig. 5 The effects of E-6801 and donepezil on the discrimination ratio (calculated from novel object exploration/(novel+ familiar object exploration) in Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is therefore an apparent paradox that E-6801, a full 5-HT 6 receptor agonist in in vitro studies (Holenz et al 2005;Romero et al 2006Romero et al , 2007, caused a dose-related restoration of natural forget- Fig. 5 The effects of E-6801 and donepezil on the discrimination ratio (calculated from novel object exploration/(novel+ familiar object exploration) in Fig.…”
Section: Discussionmentioning
confidence: 98%
“…More recently, several research groups have identified selective, high-affinity 5-HT 6 receptor full and partial agonists Glennon et al 2000;Holenz et al 2005;Mattsson et al 2005;Romero et al 2006Romero et al , 2007Schechter et al 2004Schechter et al , 2007. The few investigations carried out to date suggest that 5-HT 6 receptor agonists impair recognition memory in social recognition (Loiseau et al 2008) and short-and long-term memories in autoshaping tasks (Meneses et al 2008).…”
Section: Introductionmentioning
confidence: 95%
“…Even though reductions in total levels of cAMP were found, probably representing neurodegeneration, it is notable that cAMP is generated by many different receptors, and the fraction generated by 5-HT 6 receptors is probably very small with respect to the total receptor stimulated levels of cAMP. Therefore, cAMP formation related to 5-HT 6 receptor activation was measured as the amount of cAMP formation after 5-HT 6 receptor activation by the selective agonist E-6801 [31]. It could be argued that the decreases in E-6801 induced cAMP formation found in AD may be due to the decreases in 5-HT 6 receptor density.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were an autopsied subset of subjects included in a prospective study of behavioral changes in clinically diagnosed demented patients [15]. At entry to the study, assessment and diagnoses were made using CAMDEX [31], DMS-III-R criteria [1] and NINCDS-ADRA criteria [24]. Drug histories were recorded for all patients; 21 patients were taking tranquilizers (neuroleptics, sedative-hypnotics or antidepressants).…”
Section: Patients and Assessment Of Behaviormentioning
confidence: 99%
“…In addition, 5-HT 6 receptor agonists might be useful for their promemory and/or antiamnesic effects (Woods et al, 2012) acting on the cholinergic and/or glutamatergic neurons or alternatively; 5-HT 6 receptor antagonists and agonists might operate via modulation of distinct intracellular signaling pathways (de Foubert et al, 2007;Liu and Robichaud, 2009;Romero et al, 2006;Woods et al, 2012). As already noted (see above), density and 5-HT 6 levels were significantly decreased in a cohort of AD patients (Marcos et al, 2008).…”
Section: -Ht Neural Markers and Memorymentioning
confidence: 73%